2008
DOI: 10.1530/rep-08-0268
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the effect of angiotensin II on bovine oocyte nuclear maturation is mediated by prostaglandins E2 and F2α

Abstract: Angiotensin II (AngII) prevents the inhibitory effect of follicular cells on oocyte maturation, but its involvement in LH-induced meiotic resumption remains unknown. The aim of this study was to assess the involvement of AngII in LH-induced meiotic resumption and of prostaglandins (PGs) in the action of AngII. In the experiment I, seven cows were superovulated, intrafollicularly injected with 10 mM saralasin (a competitive AngII antagonist) or saline when the follicles reached a diameter larger than 12 mm, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…9 In contrast, the AT2 blocker inhibited ovulation and oocyte maturation. [10][11][12] It is suggested that in extra-renal tissues there are other enzymes that may be responsible for the production of AngII. 13,14 Husain et al 4 obtained AngII in vitro from angiotensinogen, using plasminogen activator as catalyst enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast, the AT2 blocker inhibited ovulation and oocyte maturation. [10][11][12] It is suggested that in extra-renal tissues there are other enzymes that may be responsible for the production of AngII. 13,14 Husain et al 4 obtained AngII in vitro from angiotensinogen, using plasminogen activator as catalyst enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is important to consider that GnRH induces a transitory increase in LH that lasts for 6 h whereas after porcine LH (pLH) injection its levels remain elevated for about 20 h (Behrouzi et al, 2016). If the research goal is to assess oocyte meiotic resumption, FSH can be used before GnRH or LH treatment to increase the number of follicles per cow (Barreta et al, 2008;Siqueira et al, 2012).…”
Section: Induction Of a New Follicular Wave And Ovulationmentioning
confidence: 99%
“…Superovulation followed by multiple intrafollicular injections and ovariectomy enables examination of factors involved in meiotic resumption after GnRH challenge (Barreta et al, 2008).…”
Section: Ovulation-related Eventsmentioning
confidence: 99%
See 2 more Smart Citations